2006 IEEE Conference on Electrical Insulation and Dielectric Phenomena 2006
DOI: 10.1109/ceidp.2006.311959
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Electrical Behavior of Treated ZnO-EPDM Nanocomposites

Abstract: Highly nonlinear electrically insulating materials have applications in high voltage cable applications. In this contribution, nanocomposites were prepared by blending ZnO nanoparticles or ZnO nanoparticles treated with aqueous SnX 2 (X= F or Cl), with EPDM (ethylene propylene diene monomer). The treated powders were a heterogeneous mixture of ZnO and SnO and show enhanced nonlinearity compared to pure ZnO. It was demonstrated that at certain filler concentrations, the resulting nanocomposites exhibited highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Wang et al [ 58 ] fabricated a composite with EPDM and 20 vol.% ZnO nanoparticles or 20 vol.% ZnO nanoparticles treated with aqueous SnX 2 (X = F or Cl). The particles had a size of 63 nm.…”
Section: Polymer Composites With a Single Particle Typementioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al [ 58 ] fabricated a composite with EPDM and 20 vol.% ZnO nanoparticles or 20 vol.% ZnO nanoparticles treated with aqueous SnX 2 (X = F or Cl). The particles had a size of 63 nm.…”
Section: Polymer Composites With a Single Particle Typementioning
confidence: 99%
“…As shown in Figure 14 a, the treated fillers showed enhanced nonlinear conduction compared to pure ZnO [ 58 ]. With controlled treatments, the conductivity can remain constant at low field, and the onset of nonlinearity and the nonlinear coefficient can be adjusted through surface treatment [ 58 ]. For example, by increasing the concentration of SnF 2 solution, the conductivity of fillers can be increased [ 58 ].…”
Section: Polymer Composites With a Single Particle Typementioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that the improved tribo-performance of the nano composite was attributable to the mechanical properties of the nano particles. In addition, ceramic fillers, such as ZnO, have well-known, non-linear behaviors, which were studied by Wang et al [19]. ZnO/EPDM (ethylene propylene diene monomer) nanocomposites were processed by melt blending in their research.…”
Section: Introductionmentioning
confidence: 99%